2016
DOI: 10.1186/s13568-016-0281-1
|View full text |Cite
|
Sign up to set email alerts
|

Baofukang suppository promotes the repair of vaginal epithelial cells in response to Candida albicans

Abstract: Vulvovaginal candidiasis (VVC) is an opportunistic fungal infection predominantly caused by Candida albicans affecting a significant number of women of reproductive age. The Chinese medicine, the Baofukang suppository is widely used in the clinic for its antimicrobial activity and is therefore of great interest as a potential antifungal drug for the prevention of VVC. We evaluated the cytotoxic activity of the Baofukang suppository using the VK2/E6E7 vaginal epithelial cell (VEC) line. When treated with the Ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 28 publications
0
8
1
Order By: Relevance
“…Previous studies have demonstrated that functional epithelial-derived IgG (RP215 positive) is secreted by vaginal epithelial cells in vitro . This finding challenges the classical concept that B cells are the only source of immunoglobulins (Li et al, 2016). These immunoglobulins appear to participate in skin innate immunity (Jiang et al, 2015) and may serve as natural antibodies (apparently the most controversial branch of humoral immunity), which not only recognize and neutralize antigenic microbial products (Amabebe and Anumba, 2018), but also provide long-term immunological memory that improves standard azole therapy efficacy and prevents relapse (Khasbiullina and Bovin, 2015).…”
Section: Discussioncontrasting
confidence: 71%
“…Previous studies have demonstrated that functional epithelial-derived IgG (RP215 positive) is secreted by vaginal epithelial cells in vitro . This finding challenges the classical concept that B cells are the only source of immunoglobulins (Li et al, 2016). These immunoglobulins appear to participate in skin innate immunity (Jiang et al, 2015) and may serve as natural antibodies (apparently the most controversial branch of humoral immunity), which not only recognize and neutralize antigenic microbial products (Amabebe and Anumba, 2018), but also provide long-term immunological memory that improves standard azole therapy efficacy and prevents relapse (Khasbiullina and Bovin, 2015).…”
Section: Discussioncontrasting
confidence: 71%
“…However, recent evidence has demonstrated that non-B cancer cells and normal non-B cells are capable of producing Igs ( Qiu et al, 2013 ). In addition, our previous research has also confirmed that normal VECs can secrete a type of functional non-B IgG rather than sIgA, challenging the classical concept that B cells are the only source of Ig ( Li et al, 2016 ). Our study also confirms that non-B IgG expressed by VECs can be up-regulated following treatment with rhIFNα-2b alone.…”
Section: Discussionmentioning
confidence: 88%
“…Baofukang suppository, a traditional Chinese medicine, has been shown to improve the clinical symptoms in VVC patients. In vitro experiments have observed that this medication can resume the C. albicans -triggered imbalanced ratio of IL-2/IL-4 cytokines to normal, resulting in the decrease of pro-inflammatory cytokine IL-2 and the increase of anti-inflammatory cytokine IL-4 ( Li et al, 2016 ). Further, Lin and others confirmed that BBR down-regulates ratios of the relative IL-2/IL-4 cytokines expression fold in mouse primary splenocytes in the absence or presence of LPS in a preventive manner, suggesting that BBR may possess anti-inflammatory potential by shifting the Th1/Th2 balance toward Th2 polarization Lin and Lin, 2011 .…”
Section: Discussionmentioning
confidence: 99%